1998
DOI: 10.1063/1.475805
|View full text |Cite
|
Sign up to set email alerts
|

The solvation of ions in acetonitrile and acetone: A molecular Ornstein–Zernike study

Abstract: The solvation of alkali and halide ions in acetonitrile and acetone has been investigated via the molecular Ornstein–Zernike theory using the hypernetted chain approximation. Theoretical Gibbs solvation energies and solvation numbers are compared with experiments and numerical simulations. The calculated single-ion solvation energies are used to check the hypotheses serving to split-up the measured solvation energies of salts into their single-ion components. The solvation structure around the ions is discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
55
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 41 publications
2
55
0
Order By: Relevance
“…[24,26] Since an ion in solution strongly disturbs the local solvent structure, [27] a detailed knowledge of the environment is an essential prerequisite for understanding reactions in the neighbourhood of the ion. Several studies investigated solvated Li + ions in acetonitrile both experimentally with various spectroscopic techniques [28][29][30][31] and computationally with different classical molecular dynamics (MD) methods [32][33][34][35] and Monte Carlo simulations of solvated alkali and halide ions in CH 3 CN. [36] Over the past decade, DFT and ab initio calculations on [Li(CH 3 CN) n ] + and related clusters were also performed by different groups.…”
Section: Introductionmentioning
confidence: 99%
“…[24,26] Since an ion in solution strongly disturbs the local solvent structure, [27] a detailed knowledge of the environment is an essential prerequisite for understanding reactions in the neighbourhood of the ion. Several studies investigated solvated Li + ions in acetonitrile both experimentally with various spectroscopic techniques [28][29][30][31] and computationally with different classical molecular dynamics (MD) methods [32][33][34][35] and Monte Carlo simulations of solvated alkali and halide ions in CH 3 CN. [36] Over the past decade, DFT and ab initio calculations on [Li(CH 3 CN) n ] + and related clusters were also performed by different groups.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical methods that have emerged in the second part of the last century from liquid-state theories [1,2], including integral equation theory in the interactionsite [3][4][5][6][7][8] or molecular [9][10][11][12][13][14] picture, classical density functional theory (DFT) [15][16][17], or classical fields theory [18][19][20][21], have become methods of choice for many physical chemistry or chemical engineering applications [22][23][24][25]. They can yield reliable predictions for both the microscopic structure and the thermodynamic properties of molecular fluids in bulk, interfacial, or confined conditions at a much more modest computational cost than molecular-dynamics or Monte-Carlo simulations.…”
mentioning
confidence: 99%
“…Studies of the solvation of alkali metal ions in acetonitrile solvents are not as common as studies of water systems, however good numbers of reports are available in literature [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Using mass spectrometry, Megyes et al [21] found up to six acetonitrile molecules surrounding the Li + ion in the gas phase.…”
Section: Introductionmentioning
confidence: 96%
“…The clusters of an alkali metal ion solvated with acetonitrile molecules have also been studied by many theoretical calculations in the past decades [30][31][32][33][34][35][36][37][38][39][40]. Various theoretical simulations have been made to describe the solvation of cations in acetonitrile molecules with, usually employing empirical/semi-empirical/realistic potential functions [30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%